Human Rights and Climate Change - Jelena Belic; Margaretha Wewerinke-Singh; Tim Meijers (Global justice: Theory, Practice, Rhetoric)
Since their recognition and institutionalization in the aftermath of World War II, human rights have been understood as protecting the fundamental interests of human beings worldwide against serious threats. Although the range of threats can be very broad, international human rights law has tended to focus on those that originate in actions or omissions of states concerning those who find themselves under their jurisdiction. It will come as no surprise, then, that the major international human rights instruments, including the International Bill of Rights, make no references to environmental threats, which are often transboundary in nature. This special issue, comprising five contributions, sheds light on different aspects of such human rights evolving in response to the distinctive threat of anthropogenic climate change. The contributions address the range of issues that have been overlooked in philosophical and legal debates.